2022
DOI: 10.3390/nu14050961
|View full text |Cite
|
Sign up to set email alerts
|

The Potential of L-Arginine in Prevention and Treatment of Disturbed Carbohydrate and Lipid Metabolism—A Review

Abstract: L-arginine, an endogenous amino acid, is a safe substance that can be found in food. The compound is involved in synthesis of various products responsible for regulatory functions in the body. Particularly noteworthy is, among others, nitric oxide, a signaling molecule regulating carbohydrate and lipid metabolism. The increasing experimental and clinical data indicate that L-arginine supplementation may be helpful in managing disturbed metabolism in obesity, regulate arterial blood pressure or alleviate type 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 98 publications
0
34
0
Order By: Relevance
“…Experimental and clinical studies have demonstrated that the induction of arginase activity in obesity is associated with endothelial dysfunction [ 147 , 149 , 150 , 151 ]. L-arginine supplementation has attracted much attention as a possible therapeutic option for endothelial dysfunction, through amelioration of NO production, insulin sensitivity, oxidative stress, and inflammation [ 152 ]. Indeed, a meta-analysis has revealed that supplementation of L-arginine for 8 weeks or more significantly decreases body weight {weighted mean difference: −0.71 kg (95% CI: −1.12 kg to −0.30 kg)} and waist circumference {weighted mean difference −2.02 cm (95% CI: −3.43 cm to −0.61 cm)} [ 153 ].…”
Section: Effects Of L-arginine Supplementation On Endothelial Functio...mentioning
confidence: 99%
See 2 more Smart Citations
“…Experimental and clinical studies have demonstrated that the induction of arginase activity in obesity is associated with endothelial dysfunction [ 147 , 149 , 150 , 151 ]. L-arginine supplementation has attracted much attention as a possible therapeutic option for endothelial dysfunction, through amelioration of NO production, insulin sensitivity, oxidative stress, and inflammation [ 152 ]. Indeed, a meta-analysis has revealed that supplementation of L-arginine for 8 weeks or more significantly decreases body weight {weighted mean difference: −0.71 kg (95% CI: −1.12 kg to −0.30 kg)} and waist circumference {weighted mean difference −2.02 cm (95% CI: −3.43 cm to −0.61 cm)} [ 153 ].…”
Section: Effects Of L-arginine Supplementation On Endothelial Functio...mentioning
confidence: 99%
“…Additionally, Shiraseb F et al reported that L-arginine supplementation significantly decreases systolic blood pressure {weighted mean difference: −6.40 mmHg (95% CI: −8.76 mmHg to −4.05 mmHg)} [ 154 ]. However, previous clinical studies have demonstrated that L-arginine supplementation does not have favorable effects on NO production and endothelial function [ 152 , 155 , 156 ]. There have been conflicting results regarding the effects of L-arginine supplementation on lipid metabolism and carbohydrates [ 152 ].…”
Section: Effects Of L-arginine Supplementation On Endothelial Functio...mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the ones that can be spotted in the research most commonly and that show the greatest therapeutic potential of L-arginine are the improvement of insulin sensitivity, an increase of nitric oxide levels and vasodilation of vessels. In long-term use, L-arginine may also improve glucose tolerance and even reduce the risk of diabetes [13].…”
Section: Clinical Studiesmentioning
confidence: 99%
“…However, little is known about the mechanisms behind these effects. L-arg supplementation can lead to a significant improvement in insulin sensitivity, as well as reduce the level of inflammatory biomarkers and oxidative stress indices, most likely by causing an increase in NO levels [ 38 , 39 , 40 , 41 , 42 ].…”
Section: Introductionmentioning
confidence: 99%